2015
DOI: 10.2109/jcersj2.123.199
|View full text |Cite
|
Sign up to set email alerts
|

Performance regeneration in lanthanum strontium manganite cathode during exposure to H<sub>2</sub>O and CO<sub>2</sub> containing ambient air atmospheres

Abstract: The regenerability and stability of lanthanum strontium manganite (LSM)/yttria doped zirconia (YSZ)/LSM symmetrical cells have been examined after the cells were exposed to real-world air environment containing H 2 O and CO 2 . An alternate exposure experiment in 20% H 2 O-air and dry air has been conducted to test the reversibility of the cell degradation in H 2 O/air. Long-term experiment in 3% H 2 O-0.5% CO 2 -air, dry air, 0.5% CO 2 -air, and 10% CO 2 -air has shown the stability and regenerability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…# , and composition have been conducted based on the CALPHAD approach and compared with the experimental observations. It is predicted that MnO x is the oxide forms on the LSM surface in both biased/unbiased conditions in accordance with current experimental results and in agreement with previous observations [70,71,74,76]. Additionally, in agreement with the previous experimental data in literature [70,74], formation of SrCO 3 on the surface of LSM-20 in 10 vol.% CO 2air is also confirmed and it is concluded that SrCO 3 is more favorable to form at the lower temperatures, the higher concentration of Sr, and the lower ! "…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…# , and composition have been conducted based on the CALPHAD approach and compared with the experimental observations. It is predicted that MnO x is the oxide forms on the LSM surface in both biased/unbiased conditions in accordance with current experimental results and in agreement with previous observations [70,71,74,76]. Additionally, in agreement with the previous experimental data in literature [70,74], formation of SrCO 3 on the surface of LSM-20 in 10 vol.% CO 2air is also confirmed and it is concluded that SrCO 3 is more favorable to form at the lower temperatures, the higher concentration of Sr, and the lower ! "…”
Section: Discussionsupporting
confidence: 92%
“…However, various phases were identified ex-situ in different works. Overall, the identified secondary phases have been claimed as either SrO [69,70,74,75] or Mn oxides [71,76]. The current…”
Section: Thermodynamic Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations